PENERAPAN TEKNOLOGI ARTIFICIAL INTELLIGENCE (AI) GUNA MENDUKUNG OPERASIONAL PELABUHAN - Reskyah Fitriani; Nisrina Imtiyaz; Fuad Mahfud Assidiq (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2023)
Artificial Intelligence (AI) is a technology designed to create computer systems that are able to imitate human intellectual abilities. As time progresses, the potential demand for sea transportation increases. Managing the increase in cargo and containers in an efficient and environmentally friendly manner is currently a major challenge for port operators and the logistic industry. In addition, port operators are not only facing an increasing increase in ship traffic. On the other hand, logistics distribution flow data is an absolute thing that must be managed well by maritime world stakeholders. The only solution to all these problems and challenges is to maximize the role of artificial intelligence-based technology and information systems in the maritime environment or what we often call Artificial Intelligence (AI). Therefore, this research aims to analyze and explore the role of Artificial Intelligence (AI) to support port operations in Indonesia.